Comparing parasitological vs serological determination of Schistosoma haematobium infection prevalence in preschool and primary school-aged children: implications for control programmes. Issue 14 (28th March 2014) - WAMI, WELCOME M.; NAUSCH, NORMAN; BAUER, KATHARINA; MIDZI, NICHOLAS; GWISAI, REGGIS; SIMMONDS, PETER; MDULUZA, TAKAFIRA; WOOLHOUSE, MARK; MUTAPI, FRANCISCA
SUMMARY: To combat schistosomiasis, the World Health Organization (WHO) recommends that infection levels are determined prior to designing and implementing control programmes, as the treatment regimens depend on the population infection prevalence. However, the sensitivity of the parasitological infection diagnostic method is less reliable when infection levels are low. The aim of this study was to compare levels of Schistosoma haematobium infection obtained by the parasitological method vs serological technique. Infection levels in preschool and primary school-aged children and their implications for control programmes were also investigated. Infection prevalence based on serology was significantly higher compared with that based on parasitology for both age groups. The difference between infection levels obtained using the two methods increased with age. Consequentially, in line with the WHO guidelines, the serological method suggested a more frequent treatment regimen for this population compared with that implied by the parasitological method. These findings highlighted the presence of infection in children aged ⩽5 years, further reiterating the need for their inclusion in control programmes. Furthermore, this study demonstrated the importance of using sensitive diagnostic methods as this has implications on the required intervention controls for the population.